PERFIL AROMÁTICO DE SUCOS E FERMENTADOS DE MAÇÃ EM DIFERENTES ESTÁDIOS DE MATURAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
Apple fermented beverages are produced in Brazil with low commercial quality fruits that do not pass by rating the degree of maturation. An study becomes necessary to determine the aromatic profile of the products processed apples in different stages of maturation knowing that this can change the technological and sensory quality of the product. Thus the aim of this study was to identify and determine the differences between apple juices and apple fermented beverage elaborated with fruits from different varieties and ripening stages in the aroma profile. Analysis of fruit ripeness, preparation of products under different conditions, flavor profile, physico-chemical composition and statistical analysis for verification and determination of the differences between the juice and fermented were perfomed. The physical chemical characteristics attested the raw material ripening of the samples. The sugar content of juices and alcohol content of fermented in general increased with ripening increasing, the opposite of the evolution of acids that in most of the samples decreased with increasing ripening, as happened with the nitrogen content. Ripening stage significantly influenced the aroma composition of apple juice and apple fermented beverages. Esters, aldehydes, acids, alcohols and ketones were identified in all samples by gas chromatographic (GC), however at higher concentrations in samples of fermented mainly made of senescent apples. Regarding the juices, ripe Gala had a prominence relating to aroma concentration over other cultivars. Using a chemometric approach by principal components analysis (PCA) and hierarchical cluster analysis (HCA) were verified that fermented have a higher composition of ten volatile compounds avaliated and fewer concentration of just one compound than apple juices. In this way chemometric approach with GC techniques can be suitable parameters to differentiate apple juice and apple fermented by aroma profiles.
Keywords: sidra; compostos voláteis; cromatografia gasosa; análise multivariada; cider; volatiles compounds; gas chromatographic; multivariate techniques; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS